Reacher. Season one [videorecording (DVD)] - Santora, Nick, 1970- (Paramount, 2022)
When retired Military Police Officer Jack Reacher is arrested for a murder he did not commit, he finds himself in the middle of a deadly conspiracy full of dirty cops, shady businessmen, and scheming politicians. With nothing but his wits, he must figure out what is happening in Margrave, Georgia. The first season of REACHER is based on the international bestseller "Killing Floor" by Lee Child.